Sustainable Investment with Special Reference to Axis ESG Equity Fund - Prince, Mridu, (European Economic Letters (EEL), 2023)
Sustainable Investment is a rational way of investing wherein investors promote long term environmental and social goals along with the returns from the fund. Asset Management Companies also get an edge by getting a positive point that they not only focus on short term gains but also Environment, Social and Governance (ESG) goals. The traditional ESG approach has led investors to take a more insightful investment decision. This paper studies the performance of Axis ESG Equity Fund against its benchmark and also examines the association of the portfolio against its benchmark NIFTY 100 ESG. It has been observed that there has been significant association between selected ESG Fund and NIFTY 100 ESG and there has been significant correlation between portfolio of Axis ESG Equity Fund and its benchmark NIFTY 100 ESG.